1979
DOI: 10.1021/i360069a009
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Cobalt(II) Acetate and Cobalt(III) Acetate in Acetic Acid Solution

Abstract: Optical and ion migration experiments were carried out with acetic acid solutions of Co" and Co"' acetate. The results indicate a mononuclear structure with six ligands. The largest amount of these complexes is uncharged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 7 publications
(13 reference statements)
1
19
0
Order By: Relevance
“…It has been shown that cobalt(M) decomposes the acetic acid yielding methyl radical and carbon dioxide (Hendriks, 1979). The methyl radical formation in the p-xylene oxidation process is evidenced by the presence of CH4 in the off-gases and of methanol and methyl acetate in the mother liquor.…”
Section: B*[fex3br]mentioning
confidence: 99%
“…It has been shown that cobalt(M) decomposes the acetic acid yielding methyl radical and carbon dioxide (Hendriks, 1979). The methyl radical formation in the p-xylene oxidation process is evidenced by the presence of CH4 in the off-gases and of methanol and methyl acetate in the mother liquor.…”
Section: B*[fex3br]mentioning
confidence: 99%
“…In addition to functioning as an autoxidation initiator, Co(III) species can oxidize peracids to generate peroxy radicals (i.e., oxidation of D to generate C), and Co(II) species are readily oxidized to Co(III) by peracids (i.e., D). 82 One might also envision direct oxidation of PhI by Co(III). 82,83 The following lines of experimental evidence suggest that Co-based additives are not intimately involved in the oxidation of PhI.…”
Section: Co(oac)mentioning
confidence: 99%
“…82 One might also envision direct oxidation of PhI by Co(III). 82,83 The following lines of experimental evidence suggest that Co-based additives are not intimately involved in the oxidation of PhI. (1) Co-based promoters are not necessary for aldehyde-promoted aerobic oxidation of aryl iodide.…”
Section: Co(oac)mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is oxidized to methyl acetate according to the following equation, which summarizes both stages (Hendriks et al, 1979): formation of methyl acetate, and their kinetics can be modified by varying the reaction conditions, the methyl acetate formation was also expected to depend on given specific parameters of the oxidation process. In fact, during our investigation of the p-xylene oxidation reaction, we could verify that the methyl acetate formation is namely affected by variations in the following parameters: water concentration in the reaction medium, oxidation temperature, p-xylene oxidation rate, and catalytic system composition.…”
Section: Methyl Acetate Formationmentioning
confidence: 99%